A new therapeutic proposal for brassiere strap groove correction with injectable hyaluronic acid: a case report - Rafaela Bressan Werle; Juliana Fonte de Souza Bedin (Surgical & Cosmetic Dermatology)
Brassiere strap groove is a common aesthetic deformity in women with breast hypertrophy, resulting from chronic pressure exerted by brassiere straps on the soft tissues over the trapezius muscle, causing local tissue depression. This condition is typically treated with fat grafting, often performed simultaneously with breast reduction surgery or lipoabdominoplasty. We report the case of a patient with recurrent brassiere strap groove following prior fat grafting, successfully corrected with hyaluronic acid filler.